Policy versus the law : the reinterpretation of the ABM Treaty - Garthoff, Raymond L. (Washington, D.C. : Brookings Institution, 1987)
The book summarizes and documents the sequence of steps involved in reaching final agreement on the language of the treaty, as well as the intentions and perceptions of the negotiators as they conducted the process.
Includes bibliographical references.
rpm 24/01/2019
Loans
Keywords: Nuclear arms control; Strategic defense initiative